Language aspects of children infected with HIV - Raphaela Barroso Guedes Granzotti; Silvia Fabiana Biason de Moura Negrini; Marisa Tomoe Hebihara Fukuda; Osvaldo Massaiti Takayanagui (Revista CEFAC, 2013)
PURPOSE: to assess the lexical proficiency and the incidence of phonologic disorders in the language of children infected with HIV. METHOD: the study population consisted of 31 children between three and seven year-old. For evaluation purposes the Test of Infantile Language - ABFW was applied in the areas of phonology and vocabulary. RESULTS: the results obtained were analyzed according to the clinical criteria for the classification of the disease proposed by the CDC and regarding the immunological profile and the viral burden using the Mann-Whitney test for statistical analysis. In the vocabulary evaluation, 100% of the children presented an inappropriate response for their age in at least two distinct conceptual fields. In the phonologic evaluation, 67.7% of the assessed children were considered to be affected by some phonologic disorder. When we compared adequate and inadequate results of phonologic evaluation to the clinical and immunological parameters of AIDS such as clinical classification (p=0,16), CD4 count (p=0,37) and viral burden (p=0,82), we did not detect a statistically significant relation between language alterations and disease severity. CONCLUSION: this research has shown that the studied group presents a high risk for language disorders and that constant phonoaudiological follow-up is essential to identify the alterations in early stage.